STUDI KUALITATIF TENTANG PERALIHAN DARI REKAM MEDIS MANUAL KE REKAM MEDIS ELEKTRONIK DI RUMAH SAKIT UNIVERSITAS MATARAM - Haerani; Muhammad Habibullah Aminy; Slamet Mardiyanto Rahayu; Lale Ajeng Khalifatun Wardani; Wahyu Aprilyaningsih (Nusadaya Journal of Multidiciplinary Studies, 2024)
Along with the development of health transformation that continues to develop in Indonesia, the use of systems in hospitals must adapt to the digitalization era, for example the use of elderly medical records that have changed to electronic medical records. This study will examine how the implementation process and obstacles faced during the transition process from manual medical records to electronic medical records at the Mataram University Hospital in 2025. This study was conducted using a qualitative analysis method that was presented descriptively by means of in-depth interviews and as a data reinforcement, observation and documentation were carried out as well as triangulation to validate the data that had been obtained. From the results of the study, the author concluded that the process of transitioning from manual medical records to electronic medical records was carried out by forming an electronic medical record implementation team, namely the medical records team, the IT team and the service and nursing divisions. With the shortcomings found such as incomplete anesthesia and general consent forms, the use of manual medical records is still used and there are not enough human resources to assist in the transition process. Where this greatly affects the maximum implementation of electronic medical records.